2004
DOI: 10.1074/jbc.m409744200
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Human Copper-Zinc Superoxide Dismutase Dimers Using Chaotrope and Reductant

Abstract: The dissociation of apo-and metal-bound human copper-zinc superoxide dismutase (SOD1) dimers induced by the chaotrope guanidine hydrochloride (GdnHCl) or the reductant Tris(2-carboxyethyl)phosphine (TCEP) has been analyzed using analytical ultracentrifugation. Global fitting of sedimentation equilibrium data under native solution conditions (without GdnHCl or TCEP) demonstrate that both the apo-and metal-bound forms of SOD1 are stable dimers. Sedimentation velocity experiments show that apo-SOD1 dimers dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
231
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(245 citation statements)
references
References 70 publications
14
231
0
Order By: Relevance
“…Analysis of the velocity data for pWTand H43R revealed species with sedimentation coefficients of 1.5-2 S (Fig. S3), very similar to the values reported previously for reduced apo WT SOD1 (28). The plots of boundary fraction versus sedimentation coefficient show only a modest slope, indicating no significant population of dimers or larger aggregated species for either pWT or H43R in these experiments.…”
Section: Dsc Reveals Complex Effects Of Als-associated Mutations On Thesupporting
confidence: 86%
See 1 more Smart Citation
“…Analysis of the velocity data for pWTand H43R revealed species with sedimentation coefficients of 1.5-2 S (Fig. S3), very similar to the values reported previously for reduced apo WT SOD1 (28). The plots of boundary fraction versus sedimentation coefficient show only a modest slope, indicating no significant population of dimers or larger aggregated species for either pWT or H43R in these experiments.…”
Section: Dsc Reveals Complex Effects Of Als-associated Mutations On Thesupporting
confidence: 86%
“…High reversibility of unfolding is a prerequisite for thermodynamic analysis, which has not been reported previously for reduced apo SOD1. In previous studies, we showed that disulfide-oxidized apo and holo pWT SOD1 thermally unfold with high reversibility according to a two-state dimer unfolding mechanism (15); however, reduction or mutation of the disulfide bond in apo SOD1 greatly weakens the dimer interface (26,28,29). Measurements of thermal unfolding for reduced apo pWT are consistent with a monomer unfolding transition, showing no systematic shift in t m;app over āˆ¼20-fold range in protein concentration (7-152 Ī¼M, 0.1-2.4 mg mL āˆ’1 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the apoprotein is dimeric when the disulfide bond is intact, but it is monomeric when the disulfide bond is reduced. By contrast, the disulfide-reduced SOD1 protein is dimeric when zinc ions are bound (22). Our results, described here, demonstrate that the dimeric SOD1 apoprotein, even with its intrasubunit disulfide bonds intact, has a marked tendency to form soluble highmolecular-weight oligomers under conditions very close to physiological.…”
Section: Discussionmentioning
confidence: 56%
“…Aggregation propensity and loss of stability of SOD1 are synergistic risk factors for fALS patient disease severity (23), and it has been suggested that a common property of fALS variants in vitro and in vivo is their propensity to aggregate (24,25). A prevailing hypothesis for the mechanism of the toxicity of fALS-SOD1 variants involves dimer destabilization and dissociation into monomers, which then nucleate the formation of higher-order aggregates (13,(26)(27)(28). Indeed, variant proteins, such as the G85R SOD1 used in this study, are found as monomers in vivo (29)(30)(31).…”
mentioning
confidence: 99%